A magnetic resonance imaging study of the adhesio interthalamica in schizophrenia - Erba?ci, Hülya; Yildirim, Hanifi; Herken, Hasan; Gümüşburun, Erdem (My University, 2002)
Several recent studies have found a relationship between midline cerebral malformations (cavum septi pellucidum, absence of the adhesio interthalamica) and schizophrenia. In this study, we investigated whether the adhesio interthalamica is more often absent in patients with schizophrenia than healthy cases and whether the absence of the adhesio interthalamica may be related to the volume of the third ventricle. Twenty-six patients (11 male, 15 female) in the schizophrenia group and twenty-nine (11 male, 18 female) cases in the control group were examined by MRI. The adhesio interthalamica was found to be absent more often among patients with schizophrenia compared with control subjects and patients without adhesio interthalamica did not have significantly larger third ventricle volumes. The absence of the adhesio interthalamica may be important in explaining the association between the abnormalities of brain midline structures and schizophrenia. © 2002 Elsevier Science B.V. All rights reserved.
Keywords: Adhesio interthalamica; Schizophrenia; Thalamus